Dr. Joshua Lampert — Deep Plane Facelift — Miami - Lampert, Joshua (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Joshua Lampert, practicing in Miami, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003153; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; miami